2017
DOI: 10.1016/j.jecp.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in reading accuracy as a result of increased interletter spacing are not specific to children with dyslexia

Abstract: Recently, increased interletter spacing (LS) has been studied as a way to enhance reading fluency. It is suggested that increased LS improves reading performance, especially in poor readers. Theoretically, these findings are well substantiated as a result of diminished crowding effects. Empirically, however, findings on LS are inconclusive. In two experiments, we examined whether effects of increased LS are specific to children with dyslexia and whether increased LS affects word or sentence processing. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…It also indicates a possible resolution to conflicting evidence in the literature with regard to letter spacing. Some studies have found improved reading speed and accuracy with increased letter spacing (Hakvoort et al, 2017; Zorzi et al, 2012), whereas others have found that reading speed is optimal at the default spacing (Perea et al, 2011; van den Boer & Hakvoort, 2015). We speculate that these discrepancies could reflect differences in the statistics of letter characteristics (e.g., font, spacing, size) as experienced by sampled readers in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also indicates a possible resolution to conflicting evidence in the literature with regard to letter spacing. Some studies have found improved reading speed and accuracy with increased letter spacing (Hakvoort et al, 2017; Zorzi et al, 2012), whereas others have found that reading speed is optimal at the default spacing (Perea et al, 2011; van den Boer & Hakvoort, 2015). We speculate that these discrepancies could reflect differences in the statistics of letter characteristics (e.g., font, spacing, size) as experienced by sampled readers in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore wondered whether this effect would also be specific to frequently encountered letter spacings. This is an important question by itself because changes in letter spacing affect reading speed and children with dyslexia have been shown to be particularly impacted by spacing features (Hakvoort et al, 2017; van den Boer & Hakvoort, 2015; Zorzi et al, 2012). In addition, by testing the same participants after ∼10 months, we also asked whether improvements in reading fluency can be predicted from changes in bigram processing.…”
Section: Experiments 2: Bigram Search With Varying Letter Spacingmentioning
confidence: 99%
“…It also indicates a possible resolution to conflicting evidence in the literature with regard to letter spacing. Some studies have found improved reading speed and accuracy with increased letter spacing (Zorzi et al, 2012;Hakvoort et al, 2017), whereas others have found that reading speed is optimal at the default spacing (Perea et al, 2011;van den Boer and Hakvoort, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore wondered whether this effect would also be specific to frequently encountered letter spacings. This is an important question by itself because changes in letter spacing affect reading speed (Zorzi et al, 2012;van den Boer and Hakvoort, 2015;Hakvoort et al, 2017). In addition, by testing the same participants after ~10 months, we also asked whether improvements in reading fluency can be predicted from changes in bigram processing.…”
Section: Experiments 2: Bigram Searches With Varying Spacingmentioning
confidence: 99%
“…In addition, the crowding effect was particularly strong in dyslexic readers (Martelli et al, 2009). It was found that increasing the word and line spacing between English letters promoted reading fluency in dyslexic children (Zorzi et al, 2012) and improved reading accuracy in normal school-age children (Hakvoort et al, 2017). Previous research suggested that the size of the Chinese character visual span, i.e., the maximum number of characters that could be recognized without moving the eyes, was affected by the complexity of the characters and was mediated in large part by visual crowding (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 96%